Prevalence of Vitamin D Deficiency in Women with Polycystic Ovarian Syndrome - Komal, Sanila Gul, Saima Ahmed (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To study frequency of vitamin D deficiency in women with polycystic ovary syndrome. Study Design: Cross-sectional study Place and Duration: Bacha Khan Medical Complex, Swabi from May 2023 to Oct 2023. Materials & Methods: 100 women with polycystic ovarian syndrome with ages 20 to 45 years were included. Patients’ data including age, body mass index, illness duration, parity and residency were recorded once they gave their permission. Vitamin D insufficiency was defined as a serum 25-hydroxyvitamin D level <20 ng/ml. SPSS 22.0 was used to analyze the data. Results: Majority of the patients 40 (40%) were aged between 26-30 years, followed by 31-35 years 30 (30%) patients. Mean BMI of the patients was 27.46±6.85 kg/m2. We found that 70 (70%) patients had vitamin D deficiency. Conclusion: We concluded that patients with polycystic ovarian syndrome had a higher than expected incidence of vitamin D deficiency. Keywords: Vitamin D Deficiency, PCOS